Dual of Modulation Spaces with Variable Smoothness and Integrability - Hua Zhu (Journal of Function Spaces)
In this article, we first give a proof for the denseness of the Schwartz class in the modulation spaces with variable smoothness and integrability. Then, we study the dual spaces of such modulation spaces.